(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
Today, the service sector is one of the fastest growing sectors of the economy of Uzbekistan. In particular, banking services, which are a service organization, are constantly being improved and expanded. Under the influence of increasing competition in the financial market in recent years, marketing activities, content and goals of the bank have changed significantly. This article describes modern requirements and practical solutions for the implementation of marketing in the banking sector, describes the agent-banking system